ROZWÓJ ZAWODOWY NAUCZYCIELI JĘZYKÓW OBCYCH SZKÓŁ PAŃSTWOWYCH NIŻSZEGO SZCZEBLA – MOŻLIWOŚCI, ŹRÓDŁA MOTYWACJI I DEMOTY-WACJI - Jaroszewska, Anna (Neofilolog, 2019)
The professional development of teachers is associated with increased specialized competence and professional advancement, which usually correlate with a specific level of intrinsic and extrinsic motivation. The vagaries of Polish education and its contemporary image are not always conducive to such development and generate situations, or circumstanc-es, which demotivate some teachers, despite the availability of many possibilities for development. This article aims to present a catalogue of options for teacher development. It discusses selected issues relating to the motivation and demotivation of foreign language teachers employed in the general public education system, in particular primary and lower secondary schools, with regard to engaging in professional development.